2017
DOI: 10.1080/14786419.2017.1413558
|View full text |Cite
|
Sign up to set email alerts
|

New coumarin from the roots of Prangos pabularia

Abstract: The new coumarin 1, yuganin A (7-methoxy-8-((1S,2S)-1,2,3-trihydroxy-3methylbutyl)-2H-chromen-2-one) along with nine known coumarins, heraclenol 3′-O-β-Dglucopyranoside (2), oxypeucedanin hydrate 3′-O-β-D-glucopyranoside (3), heraclenol (4), oxypeucedanin hydrate (5), osthole (6), oxypeucedanin (7), heraclenin (8), isoimperatorin (9), imperatorin (10) and the disaccharide sucrose (11), have been isolated from the roots of Prangos pabularia, and the structures of these isolated compounds were elucidated by spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 19 publications
1
22
0
Order By: Relevance
“…Recently, we reported that the roots of P. pabularia are good sources of biologically active secondary metabolites (coumarins) such as heraclenol, heraclenin, imperatorin, osthole, yuganin A, and others. Yuganin A showed potent effects on the proliferation of B16 melanoma cells [22]. In a continuation of this investigation, the current report presents the promising antidiabetic activity and the chemical composition of volatile secondary metabolites of the underground parts of P. pabularia growing wild in Tajikistan.…”
Section: Introductionmentioning
confidence: 62%
See 2 more Smart Citations
“…Recently, we reported that the roots of P. pabularia are good sources of biologically active secondary metabolites (coumarins) such as heraclenol, heraclenin, imperatorin, osthole, yuganin A, and others. Yuganin A showed potent effects on the proliferation of B16 melanoma cells [22]. In a continuation of this investigation, the current report presents the promising antidiabetic activity and the chemical composition of volatile secondary metabolites of the underground parts of P. pabularia growing wild in Tajikistan.…”
Section: Introductionmentioning
confidence: 62%
“…Forty-two compounds were identified in the volatile oil accounting for 97.3% of the composition; 5-Pentylcyclohexa-1,3-diene (44.6%), menthone (12.6%), 1-tridecyne (10.9%), and osthole (6.0%) were identified as major constituents of the volatile oil obtained from roots of P. pabularia (Table 1). The structure of the osthole was established on the basis one-dimensional (1D) NMR and electrospray ionization (ESI)-MS spectroscopic studies, respectively [22]. The chemical structures of the main components of the essential oil from the roots of P. pabularia are presented in Figure 1.…”
Section: Chemical Composition Of Essential Oilsmentioning
confidence: 99%
See 1 more Smart Citation
“…The most commonly used species of this genus are P. ferulacea and P. pabularia. The leaves of these plants are traditionally used as laxative, antihypertensive, and carminative agents and are also recommended for the treatment of digestive disorders (Dokovic et al 2004;Sagun et al 2006;Kazerooni et al 2006;Durmaz et al 2006;Ö zek et al 2007;Ahmed et al 2011a;Razavi 2012b;Farooq et al 2014a;Shokoohinia et al 2014;Namjoyan et al 2015;Seidi Damyeh et al 2016;Tabanca et al 2016;Gheisari et al 2016;Yousefi et al 2017;Delnavazi et al 2017;Kiliç et al 2017;Ozek et al 2018;Sadeghi and Bazdar 2018;Abbas-Mohammadi et al 2018;Numonov et al 2018). In Western North Iran, the essential oil from roots of P. ferulacea has been traditionally used for wound healing (Yousefi et al 2017).…”
Section: Traditional Use Of Prangos Speciesmentioning
confidence: 99%
“…The fresh fruits and roots of P. pabularia are also consumed in Tajikistan (local name: Yugan) for its putative effects in the treatment of vitiligo, and because these are considered to have tonic effects (Numonov et al 2018). In India, only P. pabularia (local names: Komal, Kurangas) is native.…”
Section: Traditional Use Of Prangos Speciesmentioning
confidence: 99%